Mathematical Foundations of Machine Learning Algorithm for Signal Processing Application - Goshu, Belay Sitotaw Goshu (International Journal of AI and Machine Learning Innovations in Electronics and Communication Technology, 2025)
This study presents a theoretically grounded enhancement to deep unfolding networks for sparse signal recovery, demonstrating that insights from optimization theory significantly improve network performance. We propose an architecture incorporating adaptive thresholding mechanisms and residual connections, informed by established convergence theory and stability analysis. Our enhanced model achieves a 35.8% reduction in reconstruction error compared to conventional learned iterative soft thresholding algorithms (LISTA), with a 50% improvement in convergence speed requiring fewer layers to reach optimal performance. The architecture also demonstrates superior noise robustness, maintaining a 30.6% performance advantage at high noise levels (σ = 0.5). These improvements validate the importance of layer-dependent thresholding strategies that balance exploration-exploitation tradeoffs and signal-adaptive processing that tailors parameters to specific signal characteristics. Furthermore, the integration of residual connections addresses vanishing update problems in deep unfolding networks, while mathematical constraints from optimization theory enhance generalization and training stability. The findings establish that incorporating domain knowledge through theoretically-justified architectural modifications produces more efficient, robust, and interpretable deep learning systems for signal processing applications. This work bridges the gap between classical optimization theory and modern deep learning, offering a framework for developing hybrid algorithms that maintain mathematical rigor while leveraging the representational power of neural networks.